2009
DOI: 10.1103/physrevb.80.180404
|View full text |Cite
|
Sign up to set email alerts
|

Exchange splitting of the threeΓ¯surface states of Ni(111) from three-dimensional spin- and angle-resolved photoemission spectroscopy

Abstract: The valence-band electronic structure of a clean Ni(111) surface is investigated by spin-resolved photoemission. At room temperature the orientation of the photoelectron spins on the Bloch sphere and the exchange splitting of surface and bulk states along the surface normal (Γ̅ ) are determined. All investigated states are found to have a sizable exchange splitting >50 meV. Since the splitting is smaller than the intrinsic line width in the spin-integrated spectrum this is only seen with a spin-resolved techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 23 publications
4
24
0
Order By: Relevance
“…In 74 For photon energies below hν = 46 eV, this state appears as a single shoulder in both theory and experiment while at higher photon energies it can be distinguished as a sharp feature. It strongly overlaps with the bulk bands of the same symmetry leading to an intense surface resonance structure in almost the complete Ni BBZ.…”
Section: Resultsmentioning
confidence: 99%
“…In 74 For photon energies below hν = 46 eV, this state appears as a single shoulder in both theory and experiment while at higher photon energies it can be distinguished as a sharp feature. It strongly overlaps with the bulk bands of the same symmetry leading to an intense surface resonance structure in almost the complete Ni BBZ.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, surface states on a Ni(111) surface are anticipated to be spin polarized due to the ferromagnetism of Ni. Therefore, Ni(111) surfaces have been intensively investigated using PES (Himpsel and Eastman, 1978;Donath, Passek, and Dose, 1993;Kutzner et al, 1997;Okuda et al, 2009) and in theory (Braun and Donath, 2002;Magaud et al, 2004;Ohwaki et al, 2006). It was revealed that Ni(111) surfaces indeed have spinpolarized surface states.…”
Section: B Spin-polarized Electron Scattering On Magnetic Substratesmentioning
confidence: 99%
“…Spin-split Shockley surface states dispersing upward in energy were found (Donath, Passek, and Dose, 1993). The spin-split surface states have an exchange splitting of 50-100 meV and a band bottom for the majorityspin electron around the Fermi energy atΓ (Donath, Passek, and Dose, 1993;Okuda et al, 2009). Thus, spin-dependent electron scattering phenomena might be investigated on Ni (111) surfaces.…”
Section: B Spin-polarized Electron Scattering On Magnetic Substratesmentioning
confidence: 99%
“…A Shockley surface state, derived from the sp band, with a majority spin component presides over the electronic structure at the Fermi level, while its minority component is unoccupied. A second surface state with minority spin character, deriving from the d-bands also exists with its counterparts [17][18][19].…”
Section: Introductionmentioning
confidence: 99%